Krisis Ekologi dan Degradasi Lingkungan Global : Literature-Based Study QS. Al-Nahl [16]: 10–17, QS. Al-Ghasyiyah [88]: 17–20, QS. Ali Imran [3]: 190–191 - Sela Sopiana; Muhammad Akmansyah; A. Fatoni; Amiruddin (STKIP Subang, 2026)
The global ecological crisis demands an educational paradigm capable of fostering holistic environmental awareness and ethics. This study analyzes the concept of nature based education in the Qur’an through a literature review of three groups of ayat kauniyah: QS. Al-Nahl [16]: 10–17, which portrays ecological systems as divine blessings and signs; QS. Al-Ghashiyah [88]: 17–20, which emphasizes observation andreflection on the structure of creation; and QS. Ali Imran [3]: 190–191, which highlights the integration of scientific contemplation and spiritual consciousness. Using a literature-based methodology, this research draws from classical and contemporary tafsir, environmental education texts, and ecological studies. The findings show that the Qur’an promotes an educational framework grounded in empirical observation,spiritual reflection, and the integration of tawhid as the foundation of ecological ethics. Islamic education holds strong potential as a solution to the ecological crisis when directed toward strengthening environmental literacy, moral awareness, and practical ecological action. This study affirms that ayat kauniyah serve as an epistemological basis that connects revelation, natural sciences, and human responsibility as stewards of the earth.